Autism screening and diagnosis in low resource settings: Challenges and opportunities to enhance research and services worldwide. Issue 5 (6th October 2015) - Durkin, Maureen S.; Elsabbagh, Mayada; Barbaro, Josephine; Gladstone, Melissa; Happe, Francesca; Hoekstra, Rosa A.; Lee, Li‐Ching; Rattazzi, Alexia; Stapel‐Wax, Jennifer; Stone, Wendy L.; Tager‐Flusberg, Helen; Thurm, Audrey; et al.
<x xml:space="preserve">Abstract</x> Most research into the epidemiology, etiology, clinical manifestations, diagnosis and treatment of autism is based on studies in high income countries. Moreover, within high income countries, individuals of high socioeconomic status are disproportionately represented among participants in autism research. Corresponding disparities in access to autism screening, diagnosis, and treatment exist globally. One of the barriers perpetuating this imbalance is the high cost of proprietary tools for diagnosing autism and for delivering evidence‐based therapies. Another barrier is the high cost of training of professionals and para‐professionals to use the tools. Open‐source and open access models provide a way to facilitate global collaboration and training. Using these models and technologies, the autism scientific community and clinicians worldwide should be able to work more effectively and efficiently than they have to date to address the global imbalance in autism knowledge and at the same time advance our understanding of autism and our ability to deliver cost‐effective services to everyone in need. Autism Res2015, 8: 473–476. © 2015 International Society for Autism Research, Wiley Periodicals, Inc.